POTOMORPHALOGICAL DIFFERENTIAL DIAGNOSTICS OF PULLOROSIS AND STREPTOCOCCOS DISEASES IN POULTRY - Kiyamova Z. N.; Elmurodov B. A. (Web of Journals Publishing, 2024)
The article describes the co-occurrence, clinical signs and pathomorphological changes of pullorosis and streptococcal diseases in chickens. Information on pathological changes in the body of birds and their differential diagnosis is given.
Keywords: Chicks, bacteria, pathogens, differential diagnosis, pullorosis, streptococcus, pathomorphology, bacteriology, yellow peritonitis, diagnosis, dystrophy, necrotic processes, inflammation.